Um olhar complexo sobre as práticas criativas docentes no ensino superior para a compreensão e a ética do gênero humano - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research arises from the following question: do professors at a private college in Anápolis/GO have characteristics of creativity and do they teach the understanding and ethics of humankind, from the perspective of Edgar Morin? Seeking to answer this question, a case study was carried out with the objective of analyzing whether/why/how the teaching praxis developed in the faculty object of study present characteristics of creativity, in a transdisciplinary perspective. Using a qualitative research approach, the study used a semi-structured interview, questionnaire and conversation circles to collect data and understand the investigated reality, based on the knowledge (teaching the understanding and ethics of the human race) proposed by Edgar Morin (2000). To support the construction of the epistemology of the research and promote the analysis of the collected data, we discuss the theoretical references on complexity, transdisciplinarity, ethics and creativity. We start with authors such as Edgar Morin, Maria Cândida Moraes, Vera Maria Candau, g the theory that underpins the present work, interweaving ethics, complexity, transdisciplinarity and creativity. Thus, the questions proposed to teachers are presented, which allow understanding, from their perspective, their praxis with creative potential, to teach the understanding and ethics of the human race. The answers obtained from the semi-structured interviews, questionnaires, field diary notes and conversation circles are presented as a result of the research, demonstrating the presence of necessary knowledge for the education of the future, proposed by Morin (2000). But beyond that, the case study helps to understand how teachers understand their actions and what paths they usually follow in their educational practices that contribute to creative, transdisciplinary and ethical teaching. These are the difficulties reported and the professors' efforts to provide empirical material to understand the performance of higher education professors in the face of the difficulties imposed by the SARS-CoV-2 pandemic. Therefore, we believe that knowing the different realities of teachers and their motivations to enhance reinvention, reconstruction and self-ecoorganization in different contexts is fundamental for the development of this study. In addition, we understand that the research contributes to strengthening the theoretical relationships proposed here, allowing other researches to go deeper into the propositions and concerns raised here.
A complex look at creative teaching practices in higher education for the understanding and ethics of humankind
Keywords: Educação Superior; Educação Superior - Pensar complexo; Educação Superior - Transdisciplinaridade; Educação Superior - Criatividade.; College Education; College Education - Think Complex; College Education - Transdisciplinary; College Education - Creative; CIENCIAS HUMANAS::EDUCACAO